EVALUATION OF SERUM-FREE IRON AND GLYCATED HEMOGLOBIN IN UNCONTROLLED TYPE-II DIABETIC PATIENTS - r, Kamalam; Ganesan, Nalini; m, Anbazhagan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Diabetes mellitus (DM) is a common health problem in the world. Free iron may contribute to the pathogenesis and progress of this disease and its complication. Iron causes hyperinsulinemia by decreasing the insulin uptake and metabolism by hepatocytes. Elevated iron stores are commonly found in insulin resistance. Iron in its free form is known to induce oxidation of biomolecules by producing harmful hydroxyl radicals. In this study, we aimed to estimate and compare the serum levels of free iron in diabetes and healthy individuals. Methods: This study included 244 subjects in two groups. Group-I comprised 204 subjects with DM and Group-II comprised 40 healthy subjects. Blood sugar, free iron, and glycated hemoglobin were analyzed in blood samples using standard kits. The results of all the parameters were expressed as meanÂ±standard deviation. Student t-test was done to assess the statistical significance between two groups. The association between the parameters was studied by Pearson correlation. Results: In this study, we found a significant increase in serum free iron in Group-I (p<0.01) when compared with Group-II. A significant correlation between the serum free iron and glycated hemoglobin (r=0.59; p<0.001) and fasting blood sugar (r=0.43; p<0.001). Conclusion: The elevated serum free iron in uncontrolled diabetes may contribute to oxidative stress which may be associated with complications of diabetes. Keywords: Free iron, Glycated hemoglobin, Hyperinsulinemia, Diabetes mellitus.